Karya Sastra sebagai Alternatif Media Pembelajaran pada Mata Kuliah Bimbingan dan Konseling Populasi Khusus - Ikhsan, Muhamad (Jurnal Artikula, 2023)
Learning media has an important role in conveying teaching material. Without relevant learning media, the teaching material delivered will not be as expected. Innovation is needed in determining learning media so that it can provide a constructive, creative and enjoyable lecture atmosphere. This article is a conceptual study of the use of literary works as an alternative learning medium. The aim of this research is to explain how to utilize literary works in teaching the Guidance and Counseling course for Special Populations. The method used in this study uses a phenomenological perspective, namely conducting an analytical study based on teaching practices in the Special Population Guidance and Counseling course using literary media. Observations made using literary teaching media are used as a basis for writing conceptual studies. The results and recommendations given are to utilize the richness of literary texts as alternative media in learning guidance and counseling courses for Special Populations in the Guidance and Counseling study program. Through literary media, theoretical abilities in analyzing the character of special populations can be more easily understood and put into direct practice